Somite Compartments in Amphioxus and Its Implications on the Evolution of the Vertebrate Skeletal Tissues - Yong, Luok Wen; Lu, Tsai-Ming; Tung, Che-Huang; Chiou, Ruei-Jen; Li, Kun-Lung; Yu, Jr-Kai (Frontiers in Cell and Developmental Biology, 2021)
Mineralized skeletal tissues of vertebrates are an evolutionary novelty within the chordate lineage. While the progenitor cells that contribute to vertebrate skeletal tissues are known to have two embryonic origins, the mesoderm and neural crest, the evolutionary origin of their developmental process remains unclear. Using cephalochordate amphioxus as our model, we found that cells at the lateral wall of the amphioxus somite express SPARC (a crucial gene for tissue mineralization) and various collagen genes. During development, some of these cells expand medially to surround the axial structures, including the neural tube, notochord and gut, while others expand laterally and ventrally to underlie the epidermis. Eventually these cell populations become are found closely associated with the collagenous matrix around the neural tube, notochord, and dorsal aorta, and also with the dense collagen sheets underneath the epidermis. Using known genetic markers for distinct vertebrate somite compartments, we showed that the lateral wall of amphioxus somite likely corresponds to the vertebrate dermomyotome and lateral plate mesoderm. Furthermore, we demonstrated a conserved role for BMP signaling pathway in somite patterning of both amphioxus and vertebrates. These results suggest that compartmentalized somites and their contribution to primitive skeletal tissues are ancient traits that date back to the chordate common ancestor. The finding of SPARC-expressing skeletal scaffold in amphioxus further supports supports previous hypothesis regarding the role of SPARC gene family expansion in the elaboration of the vertebrate mineralized skeleton